Hydromagnetic Flow of Heat and Mass Transfer in a Nano Williamson Fluid Past a Vertical Plate With Thermal and Momentum Slip Effects: Numerical Study - Nagendra N.; Amanulla CH.; Reddy M. Sudhakar; Prasad V. Ramachandra (Nonlinear Engineering, 2019)
In this article, the study of heat, momentum and mass (species) transfer in an electro-conductive polymer on the external surface of a vertical plate. The effects of Brownian motion and thermophoresis are incorporated in the model in the presence of both heat and nanoparticle mass transfer convective conditions. The Williamson viscoelastic model is employed which is representative of certain industrial polymers. The non-dimensional, transformed boundary layer equations for momentum and energy are solved with the second order accurate implicit Keller box finite difference method under appropriate boundary conditions. The influence of Weissenberg number, magnetic body force parameter, thermal slip parameter, hydrodynamic slip parameter, stream wise variable and Prandtl number on thermo fluid characteristics are presented graphically and discussed. A weak elevation in temperature accompanies increasing Weissenberg number whereas a significant acceleration in the flow is computed near the plate surface. Rate of heat transfer is reduced with increases the Weissenberg number. The study is relevant to enrobing processes for electric-conductive nano-materials, of potential use in aerospace, smart coating transport phenomena and other industries.